SUKU DUANO DI DESA BELARAS KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Arip, Muhammad; ', Jonyanis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Duano tribe has similarities with the Malay tribe, namely in terms of physical appearance, way of dressing, traditional customs and religious practices. This form of equality can be said to be a shared inheritance from previous generations. The aspects that are often adapted are in terms of economic, political, socio-cultural activities and marital relations. The identification of the problem in this research is how the social structure of life, social relations, economic relations, of the Duano tribe and other tribes. The aim of this research is to find out the social structure of life, social relations, economic relations, of the Duano tribe and other tribes in the village. Belaras, Mandah District, Indragiri Hilir Regency. In this research, the researcher used a type of research with a descriptive qualitative research method with ethnographic studies. The ethnographic research method is included in the qualitative research group whose characteristics are